Transcriptomic and Functional Analyses of Phenotypic Plasticity in a Higher Termite, Macrotermes barneyi Light - Sun, Pengdong; Li, Ganghua; Jian, Jianbo; Liu, Long; Chen, Junhui; Yu, Shuxin; Xu, Huan; Lei, Chaoliang; Zhou, Xuguo; Huang, Qiuying (Frontiers in Genetics, 2019)
Eusocial termites have a complex caste system, which leads to the division of labor. Previous studies offered some insight into the caste differentiation in lower termites; however, few studies were focusing on the molecular mechanisms of higher termites with sophisticated societies. Comparative transcriptomic analyses of five immature castes of a higher termite, Macrotermes barneyi Light, suggest that phenotypic plasticity is modulated by an array of transcriptional changes, including differentially expressed genes (e.g., caste-biased genes Vtg and TnC), co-expression networks (e.g., genes associated with nymph reproduction), and alternative splicing (e.g., events related to muscle development in presoldiers). Transcriptional (RT-PCR and RT-qPCR) and functional (in vivo RNAi) validation studies reveal multiple molecular mechanisms contributing to the phenotypic plasticity in eusocial termites. Molecular mechanisms governing the phenotypic plasticity in M. barneyi could be a rule rather than an exception in the evolution of sociality.